Assessment of the Water Quality of the Tigris River in the City of Mosul - Muhammed, F. I.; Akmirza, Ilker (Mustansiriyah University College of Engineering, 2025)
In this study, a total of 120 water samples were collected from five stations along the Tigris River within Mosul City and tested to assess their quality. Water samples were collected over the course of a year. The study included determining thirteen physical, chemical, and biological parameters of the water. The water quality assessment for river water was done using the Weighted Arithmetic Water Quality Index Method (WA WQI), the Canadian Council of Ministry of Environment (CCME WQI), and the method developed by Erdenebayar. The test results showed that the parameters included in the study were within the allowable limits. The overall results of the water quality index revealed that the water quality can be classified as good, which means that the water still meets the different domestic, industrial, aquatic life, and agricultural needs. The maximum water quality index values were 36, 81, and 79, and the minimum values were 18, 76, and 35 for the WA WQI, CCME WQI, and E WQI methods, respectively. A slight difference in water quality was detected during the different seasons, with a slight deterioration in its quality as water flows from north to south. Generally, a good agreement was observed among the three methods. © 2025 Elsevier B.V., All rights reserved.
Keywords: Climate Change; Erdenebayar; Mosul; Pollution; River; Water Quality Index